Ask Questions, Get Answers

Questions  >>  CBSE XII  >>  Math  >>  Differential Equations

Find a particular solution of the differential equation $(x+1)\frac{dy}{dx}=2e^{-y} -1$, given that $y = 0$ when $x = 0$.

$\begin{array}{1 1}y=\log\frac{|2x+1|}{|x-1|} \\y=\log\frac{|2x-1|}{|x+1|} \\ y=\log\large\frac{|2x+1|}{|x+1|} \\y=\log\large\frac{|2x-1|}{|x-1|} \end{array}$

1 Answer

  • The linear differential equationof the form $\large\frac{dy}{dx}$$ = F(x,y)$, where $F(x,y)$ is of the form g(x).h(y), where g(x) is a function of x and h(y) is a function of y,is called variables seperable type. This can be solved by separating the variables.
Step 1:
Given : $(x+1)\large\frac{dy}{dx}$$ = 2e^{-y }- 1$
Using the information in the tool box we understand that the equation is variables seperable type.
$\large\frac{dy}{(2e^{-y} - 1)} = \large\frac{dx}{(x+1)}$
Multiply and divide LHS by $e^y$ we get,
Step 2:
Integrating on both sides,
LHS can be integrated by substitution method
Let $2-e^y=t$
$\int \large\frac{-dt}{t}$$=-\log t$
Substituting for $t$ we get,
$-\log (2-e^t)$
Step 3:
integrating RHS we get
$\int \large\frac{dx}{(x+1)}$$=\log(x+1)$
$- \log(2-e^t) =\log(x+1) + \log C$
$\log|x+1| +\log|2-e^y| = \log C$
$\log(2-e^y).(x+1)=\log C$
$(2 - e^y)(x+1) = C$-------(1)
Step 4:
To evaluate C, let us substitute for $x = 0$ and $y = 0$
$(2 - e^0)((0+1) = C$
Step 5:
Substitute $C$ in equ(1) we get,
This is the required solution.
Help Clay6 to be free
Clay6 needs your help to survive. We have roughly 7 lakh students visiting us monthly. We want to keep our services free and improve with prompt help and advanced solutions by adding more teachers and infrastructure.

A small donation from you will help us reach that goal faster. Talk to your parents, teachers and school and spread the word about clay6. You can pay online or send a cheque.

Thanks for your support.
Please choose your payment mode to continue
Home Ask Homework Questions